Efektivitas Penerapan Cognitive Stimulation Therapy (CST) untuk Meningkatkan Fungsi Kognitif, Activity Daily living, Psikologis, dan Kualitas Hidup Pada Lansia - Lia Juniarni; Lisa Lusiana Haerunnisa (Kelompok Peneliti Muda Universitas Negeri Jakarta, 2021)
Cognitive Decline is a significant cognitive decline from normal cognition to dementia, so interventions are needed to inhibit the development of cognitive decline so that cognitive function does not decline (Smith & Blumenthal, 2016). Various efforts can be made to prevent the decline in cognitive function, namely by pharmacological and non-pharmacological collaborative therapy. Cognitive Stimulation Therapy (CST) is a non-pharmacological therapy that is effective in specifically improving cognitive function and increasing independence, reducing depression, and improving the quality of life of the elderly with dementia. The purpose of this study was to assess the Effectiveness of the Application of Cognitive Stimulation Therapy (CST) to Improve Cognitive Function, Activity Daily living, Psychological (reducing depression), and Quality of Life. This was quasi-experimental study with Two Group (pre-test and post-test), the inclusion criteria was: elderly over 60 years old with mild to moderate dementia. Therapy was carried out in 14 sessions in intervention groups, held 2 times a week for 7 weeks with a duration of 40-45 minutes. The results showed a significant difference between the pre-test and post-test in the intervention group and the control group in 3 domains, namely cognitive function p-value (0.029), depression p-value (0.02) and quality of life p-value (0.03). It was found that there was cognitive stability and an increase in the number of scores before and after the intervention, a decrease in depression and an increase in quality of life. Suggestions for this study are expected to provide CST intervention is one of the activities that can be applied in the geriatric service unit for dementia patients.